Driving Assessment Scores with Effective Calculator Implementation - Lutsic, Sarah; Zhang, Mingyuan (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2023)
This study presented a secondary analysis of the National Assessment of Educational Progress (NAEP) dataset. The paper examined the impact of calculator exposures on eighth-grade students' 2019 NAEP mathematics assessment scores. To better understand the impact of calculator use on the mathematics achievement of eighth-grade students, this study used a quantitative descriptive research design to analyze secondary data extracted from the 2019 NAEP data set. The findings are: (1) the frequency of calculator use does not impact assessment scores during math lessons. (2) Students who practice using calculators on math tests and quizzes have higher math assessment scores. (3) Frequent primary calculator use can impact math assessment scores. (4) Students who use graphing calculators frequently score higher on math assessments. In conclusion, these findings indicate that using calculators in mathematics is impactful; however, teachers must be trained to implement them effectively.